The Mystery of Sanjaya the Founder of Mataram A Historical Analysis - Setiawan, Martin Darma (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study examines the Mataram Kingdom’s historical significance during Java’s golden age, focusing on Sanjaya’s role in its socio-political and cultural development. It investigates Sanjaya’s origins, his contributions to Mataram, cultural diffusion in ancient Java, and the region’s geopolitical landscape. A multidisciplinary approach integrates historical analysis, linguistic studies, and archaeology. By analyzing inscriptions, artifacts, and historical texts, the study explores Sanjaya’s leadership, cultural exchanges, and Java’s geopolitical context. It also considers hypotheses linking Sanjaya’s lineage to Chenla and potential ties between Java’s Rakai Panunggalan of the Shailendra dynasty and Cambodia’s King Jayavarman II. Findings reveal Sanjaya’s key role in shaping Mataram’s governance and integrating Indian influences, such as the Mahabharata, with local traditions. The study suggests a possible connection between Sanjaya and Cambodian royalty, though further evidence is needed. This research enhances the understanding of Southeast Asia’s historical dynamics, providing a nuanced perspective on ancient Java’s socio-political and cultural evolution. It contributes to academic discourse and serves as a foundation for future studies.